1995
DOI: 10.1074/jbc.270.49.29453
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Characterization of cDNA Encoding the Mouse Bifunctional ATP Sulfurylase-Adenosine 5′-Phosphosulfate Kinase

Abstract: Biosynthesis of the activated sulfate donor, adenosine 3'-phosphate 5'-phosphosulfate, involves the sequential action of two enzyme activities: ATP sulfurylase, which catalyzes the formation of adenosine 5'-phosphosulfate (APS) from ATP and free sulfate, and APS kinase, which subsequently phosphorylates APS to produce adenosine 3'-phosphate 5'-phosphosulfate. Oligonucleotide primers were derived from a human infant brain-expressed sequence tag putatively encoding a portion of APS kinase. Using these primers, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 42 publications
(45 reference statements)
0
63
0
Order By: Relevance
“…Cloning of human PAPS synthase [4,7,8] revealed that it is 98 % and 95 % identical at the amino acid level with the mouse [6] and guinea-pig (unpublished work) PAPS synthases respectively, indicating that the protein is highly conserved. Following the initial cloning of PAPS synthase, a second isoform (PAPS synthase 2) was reported for human [9] and mouse [9,10] species.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cloning of human PAPS synthase [4,7,8] revealed that it is 98 % and 95 % identical at the amino acid level with the mouse [6] and guinea-pig (unpublished work) PAPS synthases respectively, indicating that the protein is highly conserved. Following the initial cloning of PAPS synthase, a second isoform (PAPS synthase 2) was reported for human [9] and mouse [9,10] species.…”
Section: Introductionmentioning
confidence: 95%
“…Bifunctional PAPS synthase was originally cloned from the marine worm [5] and the mouse [6]. Cloning of human PAPS synthase [4,7,8] revealed that it is 98 % and 95 % identical at the amino acid level with the mouse [6] and guinea-pig (unpublished work) PAPS synthases respectively, indicating that the protein is highly conserved.…”
Section: Introductionmentioning
confidence: 99%
“…To further demonstrate the similarity between yeast and mammalian nucleotide synthesis machinery, we tested the ability of human PAPS synthesis enzymes to functionally replace those of yeast. In mammals, the ATP sulfurylase and APS kinase activities of Met3 and Met14 are expressed on a single dual-functional enzyme called PAPS synthetase (27,28) (Fig. 1B).…”
Section: ј-Nucleotidase and Lithium Toxicitymentioning
confidence: 99%
“…Sequence alignment of various monofunctional sulfurylase and kinase enzymes from lower organisms and plants, and bifunctional enzymes from animals reveal the presence of several highly conserved regions (1). Many of these conserved residues are present in motifs that have been implicated in ATP binding (P-loop) (13), phosphoryl transfer (FISP) (14), phosphodiester-cleavage (15), and pyrophosphate binding (PPloop) (16).…”
mentioning
confidence: 99%